2011
DOI: 10.2174/092986611794653905
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation and Fluorescence Quenching Between Bovine Serum Albumin and L-Cysteine Capped CdSe/CdS Quantum Dots

Abstract: Water-soluble, biological-compatible, and excellent fluorescent CdSe/CdS quantum dots (QDs) with L-cysteine as capping agent were synthesized in aqueous medium. Fluorescence (FL) spectra, absorption spectra, and transmission electron microscopy (TEM) were employed to investigate the quality of the products. The interactions between QDs and bovine serum albumin (BSA) were studied by absorption and FL titration experiments. With addition of QDs, the FL intensity of BSA was significantly quenched which can be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The first concern in the trajectory of the LipQDs following systemic administration is the possible detrimental effect of serum proteins. Circulating proteins are known for their ability to interact with particulate delivery systems yielding a protein corona . Adsorption and/or interaction with serum proteins could impede the structural properties of the liposomes, resulting in premature leakage of the cargo and altered biodistribution. , Incubation of LipQDs with serum proteins resulted in a significant increase of both size (203 ± 6 vs 114 ± 0.3 nm) and PDI value (0.76 ± 0.1 vs 0.25 ± 0.01; Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first concern in the trajectory of the LipQDs following systemic administration is the possible detrimental effect of serum proteins. Circulating proteins are known for their ability to interact with particulate delivery systems yielding a protein corona . Adsorption and/or interaction with serum proteins could impede the structural properties of the liposomes, resulting in premature leakage of the cargo and altered biodistribution. , Incubation of LipQDs with serum proteins resulted in a significant increase of both size (203 ± 6 vs 114 ± 0.3 nm) and PDI value (0.76 ± 0.1 vs 0.25 ± 0.01; Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…QDs emerged in the past decade as superior substitutes for organic dyes in diagnostics due to their remarkable photochemical/physical properties, such as high photostability, high quantum yield (QY), and remarkable capabilities for multiplexing. , These properties, combined with methods to solubilize QDs in aqueous media as well as conjugating biological molecules, have led to a great interest for the utilization of QDs as fluorescent markers in molecular, cellular, and in vivo imaging. , The toxicity of hydrophobic QDs due to organic ligands can be overcome by capping the QDs with a hydrophilic corona . Nevertheless, there are several unmet challenges in the development of QDs for theranostic use including (i) fluorescent signal reduction due to serum protein adsorption following systemic administration, (ii) enhanced quenching in the presence of oxidative or acidic conditions characterizing inflammation and lysosomal milieu, , (iii) quenching due to intracellular aggregation, (iv) the intrinsic cytotoxicity of released Cd 2+ /Se 2– , and (v) the wide systemic biodistribution. In an attempt to overcome some of the aforementioned limitations, nanocarrier systems for QD delivery have been suggested including polymeric nanoparticles (NPs), micelles, , and liposomes. However, none of these described delivery systems adequately addressed the requirements for efficient fluorescent imaging including high QY, prolonged decay lifetime, high stability in serum proteins and acidic pH, no premature leakage of QDs, high encapsulation yield, and demonstrating imaging efficacy in vitro as well as in vivo .…”
mentioning
confidence: 99%
“…However, l ‐cysteine has the greatest potential, due to the presence of carboxylic and amino groups, which can be used for further bioconjugation to other amino acids and proteins. Furthermore, l ‐cysteine binds Zn strongly and hence may act as a better capping agent from the biocompatibility point of view .…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we attempted to use a green, room temperature, aqueous synthetic route to obtain Mn:ZnS QDs capped with l ‐cysteine having a high optical response. The choice of the capping agent is based on the biological versatility of l ‐cysteine and its potential to be soluble in water . To our knowledge, this is the first report of the toxicological analysis of l ‐cysteine‐capped Mn:ZnS QDs synthesized at room temperature for use in cellular imaging.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous reports have found that the fluorescence of semiconductor QDs can be quenched by various chemical compounds existing within the cellular environment such as nucleotides and amino acids [11]. Further to this, it has been reported that semiconductor QDs can be quenched in the presence of bovine serum albumin (BSA) [12,13], a key component to any immunolabelling protocol. In this study, we label mammalian cells with commercially available QDs and provide a quantitative analysis of the fluorescence intensity of QDs excited with 280 nm light and 365 nm light, a wavelength already routinely used in light microscopy for the excitation of common fluorophores.…”
Section: Introductionmentioning
confidence: 95%